Feasibility Analysis of The 2D (Diki and Dafa) Burnt Rice Cracker Business (A case study of MSMEs of the 2D Burnt Rice Cracker at Mandirancan Street, Mandirancan District, Kuningan Regency) - Maria Qipthia Hanun; Achmad Faqih (Eduvest - Journal of Universal Studies, 2024)
This research aims to determine (1) the feasibility of the 2D Burnt Rice Cracker business in terms of financial aspects and (2) the feasibility of the 2D Burnt Rice Cracker business in terms of non-financial aspects. The research was carried out from September to December 2023. The research took a case study at Micro, Small and Medium Enterprises (MSMEs) of the 2D Burnt Rice Cracker on Mandirancan Street, Mandirancan District, Kuningan Regency. The technique for taking respondents in this research was by using saturated sampling (census). The findings of the research show that the 2D Burnt Rice Cracker business on Mandirancan Street is worth pursuing, because several criteria were obtained as follows (1) Judging from the financial aspect, the 2D Burnt Rice Cracker business is profitable and worth pursuing because it has an R/C value of 2,32, BEP production is 1,373 boxes/month while total real production reaches 3,200 boxes/month, then BEP price is Rp. 8,584 while the real price is Rp. 20,000, ROI value of 133% and payback period of 6 months: (2) Judging from the non-financial feasibility analysis including legal aspects, environmental aspects, market and marketing aspects, technical and technological aspects, management aspects and human resource aspects, the 2D Burnt Rice Cracker is worth the effort.